2004
DOI: 10.1002/uog.1048
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of preterm delivery in twin pregnancy: a prospective, observational study of cervical length and fetal fibronectin testing

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
2
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 21 publications
5
46
2
3
Order By: Relevance
“…Our observations provide evidence that this hypothesis is correct. Gibson 34 In contrast, this was not observed in other studies 34,36,[42][43][44][45][46][47][48] For example, Khalil et al reported serial measurements of cervical length in 209 women with twins at 20-23 weeks and 3-5 weeks later. 46 There were no differences in the predictive value of the first cervical length measurement, the follow-up cervical length measurement, and change in cervical length between the two measurements.…”
Section: Commentmentioning
confidence: 88%
See 3 more Smart Citations
“…Our observations provide evidence that this hypothesis is correct. Gibson 34 In contrast, this was not observed in other studies 34,36,[42][43][44][45][46][47][48] For example, Khalil et al reported serial measurements of cervical length in 209 women with twins at 20-23 weeks and 3-5 weeks later. 46 There were no differences in the predictive value of the first cervical length measurement, the follow-up cervical length measurement, and change in cervical length between the two measurements.…”
Section: Commentmentioning
confidence: 88%
“…The association between a short sonographic cervical length and the risk of subsequent PTB is well-established in singleton 11, 23-28, 52-61 and twin gestations 12,[29][30][31][32][33][34][35][36][37][38][39][40][62][63][64] . Since cervical length changes over time as the time of the onset of labor approaches, we propose that cervical shortening detected with serial sonographic examinations may yield information about the risk of PTB which is not available at the time of the routine sonographic examination in the midtrimester.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…A large number of prospective studies [20][21][22][23][24][25][26][27][28][29][30] have shown the predictive value of midtrimester cervical length measurement in twin pregnancies; these data were collected in two large meta-analyses. The first meta-analysis included 21 studies, 16 in asymptomatic women and only 5 in symptomatic women; the collected data included 3,523 women.…”
Section: Prediction Of Preterm Birthmentioning
confidence: 99%